Theory of Planned Behavior Approach to Understand the Influence of Green Perceived Risk on Consumers' Green Product Purchase Intentions in an Emerging Country - Nguyen, Thi Thu Huong; Yang, Zhi; Nguyen, Thi Thuy Nga; Thanh, Cao Thi (International Review of Management and Marketing, 2019)
Green products are increasingly prevalent in developing countries, however consumers are sometimes perceive their green purchasing decision as risky. The major problem seems to be linked to the greenwashing cases. Despite the fact that, up to now there still have no quantitative paper studying how consumers make judgments and decisions in relation to these risks. This paper applies the theory of planned behavior (TPB) to develop research framework under the circumstance of the green vegetable consumption in Vietnam as a whole in terms of green perceived risk. The present study focuses on 455 Vietnamese consumers who have been working and have experience buying green vegetable. The Exploratory factor analysis (EFA) technique and the Confirmatory factor analysis (CFA) were performed using IBM SPSS and AMOS 23 software. Testing the hypotheses and a structural equation modeling (SEM) method were conducted. This research finds out the answer for the questions of how green perceived risk affects consumer's green purchase intentions under the circumstance of an emerging country. Supported the TPB model this paper provides better predictive power of the nexus between intentions and actual behaviors. Finally, this research provides some useful implications for corporates in the marketing strategy development in accordance with environmental trend. Keywords: Green Perceived Risk, Theory of Planned Behavior, Green Purchase Intentions. JEL Classification: C12, L66, M3. DOI: https://doi.org/10.32479/irmm.7877